(Invited) Graphene Plane Electrode for Low Power 3D Resistive Random Access Memory. (4th May 2016) - Lee, Seunghyun; Sohn, Joon; Jiang, Zizhen; Chen, Hong-Yu; Wong, H. -S. Philip
Abstract : In this work, we introduce one of the world's thinnest non-volatile memory stacked in a 3-dimensional vertical structure. We exploit the edge of an atomically thin graphene layer and form a metal oxide resistive memory using HfOx as the switching oxide. We found that such thin memory has potential for highly integrated storage system with memory density higher than the same memory structure made using thin metal layer. We also confirm that it is not possible to build such thin memory with conventional metal because the sheet resistance of metal dramatically increases as it is thinned down to less than 5 nm.